2022
DOI: 10.22270/ujpr.v7i2.752
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Health Management Information System and Associated Factors in Health Institutions of Kembata Tembaro Zone, Southern Ethiopia

Abstract: Background: Health Management Information System (HMIS) is one of the six building blocks of a health system designed to provide important data for continuous quality improvement at all levels of health care administration. It is a major source of information for monitoring and adjusting policy implementation and resources use. Some studies have been conducted in health data collection and ways to improve data quality, but little is known about utilization of HMIS in health services organization. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Ethiopia, the use of routine health information for evidence-based decision-making is not different from the case of developing nations all over the world. For instance, a systematic review and meta-analysis11 as well as other independent studies conducted across the nation came to the conclusion that routine health information was not used effectively for making evidence-based decisions 12–25. The most often mentioned factors affecting routine use of health information in Ethiopia included training15 16 18 20 23 26–29 competency related to data management15 18–20 23 27 28 30 and the availability of standard guidelines (such as indicator definition guideline, Health Management Information System Recording and Reporting Procedures Manual , etc) 15 16 20 26–28 30 31…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, the use of routine health information for evidence-based decision-making is not different from the case of developing nations all over the world. For instance, a systematic review and meta-analysis11 as well as other independent studies conducted across the nation came to the conclusion that routine health information was not used effectively for making evidence-based decisions 12–25. The most often mentioned factors affecting routine use of health information in Ethiopia included training15 16 18 20 23 26–29 competency related to data management15 18–20 23 27 28 30 and the availability of standard guidelines (such as indicator definition guideline, Health Management Information System Recording and Reporting Procedures Manual , etc) 15 16 20 26–28 30 31…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in the Kembata Tembaro Zone, Ethiopia reported that the use of SIKR in health institutions was influenced by training on CIC management, supportive supervision and the presence of procedures were positively associated with the use of SIKR (Kondoro et al, 2022). Health facilities and agencies should increase the capacity of health workers through the recommended training and supportive supervision.…”
Section: Introductionmentioning
confidence: 99%